Pensamento e infância: práticas da educação infantil em tempos de interesse - Venturini, Gabriela (Universidade do Vale do Rio dos Sinos, 2019)
This thesis aims to analyze how the concept of thought is described in the three main documents that govern Brazilian Early Child Education in the present (National Education Guidelines and Framework Law/1996 – Lei de Diretrizes e Bases da Educação Nacional/1996, National Curricular Guidelines for Early Childhood Education/2010 - Diretrizes Curriculares Nacionais para a Educação Infantil/2010, and Common National Curricular Basis/2018 – Base Nacional Comum Curricular/2018) and what its implications for the relation between childhood and thought. Therefore, it is based on a perspective of philosophy, on the study of difference, to examine the discursive practices that circulate in these documents and that imply in ways of doing education, in schools of Early Childhood Education, when focusing the concept of crossed thinking by discourse of interest in the contemporary. In addition to the concepts of thought and interest, which guide all research, others have also been studied in this research, such as: child education, children, childhood, time, leisure and experience. The theoretical basis used were the studies of Foucault, López, Kohan, Larrosa, Saballa, Dornelles, Bujes, Horn, Corazza, Ribeiro, among others. Thus, analyzes were mapped by the dating of the documents in order to observe the regularities and displacements in the relations between childhood and thought when strongly crossed by the discourse of interest, as pointed out from the examination of these texts. Based on this analytical movement and with inspiration in the Foucauldian discourse analysis, was observed a force of discursive practices about the interests of children as the other one of the thought when taken within a philosophical perspective of the difference. Therefore, it was found that such documents marked the guarantee of rights of imminent importance for children, such as the right to learn, the expansion of cultural repertoire and freedom of thought. However, it has also been found that such materials, implanted in the midst of many political struggles, operate thinking as problem solving from a logic of recognition, with a neoliberal logic of interest that is increasingly shifting to an individual interest of the an entrepreneurial subject of self and a society of performance, focused on the recording of children's production, producing ways of relating to the thought in this space that is the school of Early Childhood Education. With this, was aimed to think of a break in the midst of the breaches found, not to denounce, but to take the power of thought in pre-school schools when crossed by the need of the leisure-time and the experience of thought.
Keywords: Pensamento; Infância; Interesse; Educação Infantil; Tempo do ócio; Thought; Childhood; Interest; Early; Childhood Education; ACCNPQ::Ciências Humanas::Educação